If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5w + -5 = 5w + 5 Reorder the terms: -5 + 5w = 5w + 5 Reorder the terms: -5 + 5w = 5 + 5w Add '-5w' to each side of the equation. -5 + 5w + -5w = 5 + 5w + -5w Combine like terms: 5w + -5w = 0 -5 + 0 = 5 + 5w + -5w -5 = 5 + 5w + -5w Combine like terms: 5w + -5w = 0 -5 = 5 + 0 -5 = 5 Solving -5 = 5 Couldn't find a variable to solve for. This equation is invalid, the left and right sides are not equal, therefore there is no solution.
| 36x+2=4 | | 2-16t=(-3t+2) | | 0.13y+0.05(y+6000)=1380 | | 18r=24r^2 | | 15y^2-15y+7=0 | | 2p(6p-18)=0 | | (x-9)(2x+4)=0 | | 25x^2/(5x-2) | | 7x-3=67forx | | 12x+72-30= | | 3h^2+6h=0 | | -3/7x=-6 | | f(5)=(2x-8) | | 16x^4+22x^3-4x^2= | | 4x^2-1x+1=0 | | 3x√35/7 | | 6m^5/2m^2 | | 2(X-15)=X/2 | | f(4)=(2x-8) | | 4x^2-1=63 | | f(1/3)=3x-1 | | 5x×2=210/3 | | 7r(p+4q)-5(p+4q)= | | .002=(4/3)3.14*r^3 | | 2[w-(3w+14)+8]=2(w+6) | | -10+6f=110 | | (x+4)(x-4)(x-9)= | | f(3)=(2x-8) | | 7m(m-1)=4(m-1) | | 4r(p-7q)+3(p-7q)= | | (1/2)(116-x)=20 | | f(2)=3x-1 |